2023
DOI: 10.1007/s11119-023-10018-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting site-specific economic optimal nitrogen rate using machine learning methods and on-farm precision experimentation

Abstract: Applying at the economic optimal nitrogen rate (EONR) has the potential to increase nitrogen (N) fertilization efficiency and profits while reducing negative environmental impacts. On-farm precision experimentation (OFPE) provides the opportunity to collect large amounts of data to estimate the EONR. Machine learning (ML) methods such as generalized additive models (GAM) and random forest (RF) are promising methods for estimating yields and EONR. Twenty OFPE N trials in wheat and barley were conducted and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…There is much to learn and improve in this area of ML prediction. Researchers have concluded that as technology improves, there is great opportunity to employ ML, but today more research is required to widely deploy it for N rate predictions (de Lara et al., 2023; Chlingaryan et al., 2018).
…”
Section: Applications For Machine Learning In 4r Nutrient Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…There is much to learn and improve in this area of ML prediction. Researchers have concluded that as technology improves, there is great opportunity to employ ML, but today more research is required to widely deploy it for N rate predictions (de Lara et al., 2023; Chlingaryan et al., 2018).
…”
Section: Applications For Machine Learning In 4r Nutrient Managementmentioning
confidence: 99%
“…A 2022 study in of canola production in Canada found that using ML models could reasonably predict optimal N rates for split applications when historical and current weather conditions were included in the model (Wen et al., 2022). However, a Nebraska study in corn found that ML models built from data in one field could not be used to accurately predict N rates in other fields (de Lara et al., 2023). There is much to learn and improve in this area of ML prediction.…”
Section: Applications For Machine Learning In 4r Nutrient Managementmentioning
confidence: 99%
“…A 2022 study in of canola production in Canada found that using ML models could reasonably predict optimal N rates for split applications when historical and current weather conditions were included in the model (Wen et al, 2022). However, a Nebraska study in corn found that ML models built from data in one field could not be used to accurately predict N rates in other fields (de Lara et al, 2023). There is much to learn and improve in this area of ML prediction.…”
Section: Data Privacymentioning
confidence: 99%
“…There is much to learn and improve in this area of ML prediction. Researchers have concluded that as technology improves, there is great opportunity to employ ML, but today more research is required to widely deploy it for N rate predictions (de Lara et al, 2023;Chlingaryan et al, 2018).…”
Section: Data Privacymentioning
confidence: 99%
“…One can then plug in site-specific soil/ field characteristics to the estimated model to represent site-specific yield response functions. A variety of statistical methods are employed within this framework, including spatial econometrics (Anselin et al, 2004;Liu et al, 2006) and various machine learning techniques like random forests (Krause et al, 2020;Lara et al, 2023), convolutional neural networks (Barbosa et al, 2020), and causal forests (Kakimoto et al, 2022). The second approach is characteristic-agnostic, represented by geographically weighted regression (GWR).…”
mentioning
confidence: 99%